Incidence and predictors of total mortality in 267 adults presenting with mitochondrial diseases. Issue 3 (26th November 2019) - Papadopoulos, Constantinos; Wahbi, Karim; Behin, Anthony; Bougouin, Wulfran; Stojkovic, Tanya; Leonard‐Louis, Sarah; Berber, Nawal; Lombès, Anne; Duboc, Denis; Jardel, Claude; Eymard, Bruno; Laforêt, Pascal
Abstract: Assessing long‐term mortality and identifying predictors of death in adults with mitochondrial diseases. We retrospectively included adult patients with genetically proven mitochondrial diseases referred to our centre between January 2000 and June 2016, and collected information relative to their genetic testing, clinical assessments, and vital status. We performed single and multiple variable analyses in search of predictors of total mortality, and calculated hazard ratios (HR) and 95% confidence intervals (CI). We included 267 patients (women 59%; median age 43.3 [31.3‐54.2] years), including 111 with mitochondrial DNA (mtDNA) single large‐scale deletions, 65 with m.3243A>G, 24 with m.8344A>G, 32 with other mtDNA point mutations, and 36 patients with nuclear genes mutations. Over a median follow‐up of 8.9 years (0.3 to 18.7), 61 patients (22.8%) died, at a median age of 50.7 (37.9‐51.9) years. Primary cause of death was cardiovascular disease in 16 patients (26.2%), respiratory in 11 (18.0%), and gastrointestinal in 5 (8.1%). By multiple variable analysis, diabetes (HR 2.75; 95% CI 1.46‐5.18), intraventricular cardiac conduction defects (HR 3.38; 95% CI 1.71‐6.76) and focal brain involvement (HR 2.39; 95% CI 1.25‐4.57) were independent predictors of death. Adult patients with mitochondrial diseases present high morbidity that can be independently predicted by the presence of diabetes, intraventricular cardiac conduction defects, and focal brain involvement.